The Activities of Customs and Tax Control Service in the Field of Gambling Market - Lik Katarzyna (Studia Ekonomiczne i Regionalne, 2019)
Gambling activity is a multifaceted phenomenon. Gambling is a special field of business. The government authorities ascribe the right to a monopoly of this area of economic activity. The randomness and financial size of gambling foster the development of the grey market. In addition to the economic effect, the moral dimension of this type of activity is an extremely important aspect. The Customs and Tax Control Service supervises the functioning of the gambling market in Poland.